Primary Schooling in Zambia Squeezed at Community and Household Level - Liv Belsby; Bjørn K. Wold (Statistics Norway, Research Department, 1997)
A part of the current economic reform program in Zambia, is to increase standard, efficiency and equity in the primary school sector. This paper studies primary school attendance. A logistic regression analysis is used to show that community level and household level variables affect the likelihood of attending primary school for children between seven and thirteen years of age. A number of community level variables have a significant effect and are also interesting from a policy point of view. Household level variables have even stronger effects. A policy conclusion: There is a need to introduce a widespread scholarship program to ensure equity and efficiency. A scientific conclusion: A multilevel analysis contributes additional insights. A final policy conclusion: There is a need to introduce a widespread scholarship program to ensure equity and efficiency. A final scientific conclusion: A a dedicated multilevel analysis might yield additional insights.
Keywords: C35; I21; O15; 330; Primary school attendance; Zambia; logistic regression model; community level; household level